ANALISIS KEJADIAN KEBAKARAN DENGAN METODE “LOSS CAUSATION MODEL” PADA SEBUAH PABRIK KAYU LAPIS DI PACITAN - Evi Yunita Karuniawati; Bina Kurniawan; Hanifa Maher Denny (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Investigation of fire incident to find its cause is a repressive rule after the accident.The Loss Causation Model is one of the causal accident theories.The purpose of this research was to analyze a fire incident using